PENINGKATAN PENGETAHUAN PBHS DAN PENERAPAN CUCI TANGAN DALAM UPAYA PENCEGAHAN COVID-19 PADA SANTRI DI LINGKUNGAN PONDOK PESANTREN - W Wahyuni; Siti fatmawati (P3M Universitas Aisyiyah Surakarta, 2020)
Pondok Pesantren is one of the educational places in Indonesia where students live together. In almost all cities you can find Islamic boarding schools with various problems. , an unhealthy environment is closely related to an increased incidence of disease. Especially with the Covid-19 pandemic, one of the behaviors that must be carried out by Pondok santri is to wash their hands with running water with soap in the hope that students can increase their knowledge of washing hands and apply it in their daily behavior in preventing Covid-19. In addition to the factor of hand washing habits that are not frequently practiced, there are also other factors that influence health behavior, namely the lack of health promotion regarding hand washing. The aim of this activity is to promote how to wash hands with soap for the prevention of Covid-19. The method in this activity is giving lectures, direct questions and answers, demonstrations of washing hands with soap, redemonstrations by students, the results of previous knowledge of washing hands 24 (34.2)% to 48 (68.8%). In conclusion there is an increase in knowledge of washing hands with soap